Hydrovolt power generation material and preparation method of power generation device of hydrovolt power generation material
TpPa-SO3H-COF and TpPa-Py-COF materials were prepared by replacing para-phenylenediamine with 2,5-diaminobenzenesulfonic acid or 2,5-diaminopyridine, and the output of existing hydrovoltaic power generation materials was solved. The problem of insufficient performance achieves efficient voltage and current output performance.
Patent Information
- Application Number
- CN202411549354.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The voltage and current output performance of existing hydrovoltaic power generation materials is insufficient, making it difficult to meet the efficient conversion needs of renewable energy.
TpPa-SO3H-COF and TpPa-Py-COF materials were prepared by replacing para-phenylenediamine with 2,5-diaminobenzenesulfonic acid or 2,5-diaminopyridine, and constructed through interfacial polymerization to increase water The electrical signal output of the volt power generator device.
The voltage and current output performance of hydrovoltaic power generation devices is significantly improved. The voltage and current output of TpPa-SO3H-COF is 1.4V and 14uA, respectively, and the voltage and current output of TpPa-Py-COF is 0.75V and 7.8uA, respectively.
Smart Images

Figure CN119431699A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic materials, and in particular relates to a preparation method of a hydroelectric power generation material and a power generation device thereof. Background Art
[0002] In recent years, global energy shortages and environmental pollution have become increasingly severe, and the global demand for renewable energy has become more urgent. Therefore, more and more countries have begun to turn to the development and utilization of renewable energy. Evaporation-induced hydrovoltaic power generation technology is an emerging power generation technology different from fuel cells. The principle is to use the evaporation of water at the solid-liquid interface to generate a streaming potential, thereby collecting thermal energy from the surrounding environment and converting it into electrical energy. In recent years, this technology has attracted the attention of researchers because of its simple and green energy conversion method. Since electrical energy essentially comes from the interaction between water molecules and materials, and the surface properties of solid materials are the main factors affecting their interaction with water molecules and evaporation-induced power generation, surface modification has become an important strategy to improve output performance.
[0003] Material surface modification mainly refers to changing the surface chemical properties of materials such as hydrophilicity, zeta potential and surface energy by introducing functional groups. For example, Zhou et al. modified hydrophilic porous carbon film with super-hydrophobic 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PFDTS) to obtain hydrophilic and hydrophobic distribution areas, and the prepared power generation device had an output voltage of 0.8V; Zhou et al. modified the surface of carbon nanoparticles with poly (sodium p-styrene sulfonate) (PSS), 1,2,3,4-butanetetracarboxylic acid (BTCA), polyethyleneimine (PEI) and poly (dimethyldiallyl ammonium chloride) (PDADMAC) to obtain different zeta potentials, and the output voltage of the prepared power generation device changed from 1.2V to 3, 2.8, -2.5 and - 1.5V; Kim et al. modified micron-sized carbon by using polystyrene sulfonic acid (PSSA) as a proton donor and polyacrylic acid / carboxymethyl cellulose (PAA / CMC) as a network adhesive. The prepared power generation device had an output voltage of 0.4V and an output current of 0.45uA; It can be seen from the above reports that designing the surface wettability of solid materials is conducive to the spontaneous penetration and directional transport of water on the film, thereby improving the electrical output power. Secondly, the surface charge density, which depends on the dissociation of charged surface functional groups in aqueous solution, also has an important influence on the output performance of the device. These surface modification methods have improved the output performance of the material to a certain extent.
[0004] Therefore, the material selection and preparation methods for hydrovoltaic power generation devices have become a hot topic in the field of power generation technology. In particular, how to use covalent organic framework (COFs) materials with high porosity, high specific surface area, adjustable structure and high stability to prepare hydrovoltaic power generation devices has become a key research topic. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention invents a method for preparing a hydroelectric power generation material and a power generation device thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A hydrovoltaic power generation material, characterized in that the hydrovoltaic power generation material is a TpPa-SO3H-COF material or a TpPa-Py-COF material prepared by replacing p-phenylenediamine with 2,5-diaminobenzenesulfonic acid or 2,5-diaminopyridine during the preparation of the TpPa-COF material.
[0008] The present invention has discovered two materials for preparing hydrovoltaic power generation devices from covalent organic framework (COFs) materials, which are constructed through interfacial polymerization reactions and effectively improve the electrical signal outputs of voltage and current of the hydrovoltaic power generation devices.
[0009] A method for preparing a power generation device, the method comprising the following steps:
[0010] S1: Transfer the TpPa-SO3H-COF material or TpPa-Py-COF material to a 100 ml beaker, add 50 ml of deionized water, and perform ultrasonic treatment on the solution in the beaker for 30 min to obtain a mixed solution A;
[0011] S2: Weigh 35 mg of silver nanoparticles into a 250 ml beaker using a high-precision electronic balance, add 190 ml of deionized water and 10 ml of isopropanol into the beaker to obtain a silver nanoparticle mixed solution, and perform ultrasonic treatment on the silver nanoparticle mixed solution for 30 min;
[0012] S3: Take an organic filter membrane and fix it at the filter of the suction filtration device, fix a waterproof plastic sheet on the organic filter membrane, pour 35 ml of the silver nanoparticle mixed solution into it, and then transfer it to a blast drying oven and dry it for 10 minutes to obtain an organic filter membrane plated with a silver electrode;
[0013] S4: fix the organic filter membrane plated with silver electrodes obtained in step S3 at the filter of the suction filtration device, pour 50 ml of mixed solution A, let the mixed solution A be evenly distributed on the organic filter membrane and cover the silver electrodes, and then transfer the organic filter membrane to a blast drying oven and dry it for 10 minutes to obtain a power generation membrane;
[0014] S5: Fix two 30 cm copper wires on the silver electrodes on both sides of the power generation membrane, and finally use hot melt adhesive to reinforce and waterproof the connection between the copper wires and the power generation membrane to obtain a hydrovoltaic power generation device.
[0015] Furthermore, in the steps S3 and S4, the drying temperature of the blast drying oven is 70° C.-100° C., and the silver electrode and the organic filter membrane are dried to solidify the electrode on the filter membrane.
[0016] Furthermore, the concentration of the silver nanoparticle solution prepared in step S2 is 1.62 mmoL / L, thereby ensuring that the silver nanoparticles are uniformly and fully attached to the organic filter membrane.
[0017] Furthermore, the overall shape of the waterproof plastic sheet is a square with a width of 5 cm, and a rectangular space with a length of 1.5 cm and a width of 0.5 cm is reserved at symmetrical positions above and below the square to ensure that the silver electrode plated on the organic filter membrane has a rectangular shape.
[0018] The advantages of the present invention are: 1. The present invention prepares TpPa-SO3H-COF and TpPa-Py-COF nanomaterials and corresponding hydrovoltaic power generation devices. Characterization results show that two covalent organic framework nanomaterials are successfully constructed through the amine-aldehyde condensation reaction (Schiff base reaction) between aldehyde monomers and amine monomers, and the surface modification of the materials is successfully achieved through functional groups with different charges on the amine monomers; 2. The constructed hydrovoltaic power generation device has good electrical energy output. The voltage and current outputs of TpPa-COF are: 0.3V and 2.2uA; the voltage and current outputs of TpPa-SO3H-COF are: 1.4V and 14uA; the voltage and current outputs of TpPa-Py-COF are: 0.75V and 7.8uA. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a surface scanning electron micrograph of TpPa-COF;
[0020] Figure 2 is a surface scanning electron micrograph of TpPa-SO3H-COF;
[0021] Figure 3 is a surface scanning electron micrograph of TpPa-Py-COF;
[0022] Figure 4 It is the X-ray diffraction analysis diagram of TpPa-COF, TpPa-SO3H-COF, and TpPa-Py-COF;
[0023] Figure 5 It is a schematic diagram of the voltage performance of the hydrovoltaic power generation devices of TpPa-COF, TpPa-SO3H-COF, and TpPa-Py-COF;
[0024] Figure 6It is a schematic diagram of the current performance of the hydrovoltaic power generation devices of TpPa-COF, TpPa-SO3H-COF, and TpPa-Py-COF;
[0025] Figure 7 This is a graph showing the output voltage and current of the hydrovoltaic power generation device based on TpPa-SO3H-COF as a function of the external load. DETAILED DESCRIPTION
[0026] The present invention is described in detail below with reference to the accompanying drawings:
[0027] A hydrovoltaic power generation material, characterized in that the hydrovoltaic power generation material is a TpPa-SO3H-COF material or a TpPa-Py-COF material prepared by replacing p-phenylenediamine with 2,5-diaminobenzenesulfonic acid or 2,5-diaminopyridine during the preparation of the TpPa-COF material.
[0028] The preparation method of the TpPa-COF material is:
[0029] (101) Weigh 12.64 mg of trialdehyde phloroglucinol using a high-precision electronic balance and add it into a 250-mL beaker;
[0030] (102) 60 mL of n-octanoic acid was added to a beaker containing 12.64 mg of trialdehyde phloroglucinol;
[0031] (103) The obtained mixed solution of trialdehyde phloroglucinol and n-octanoic acid was subjected to ultrasonic treatment for 30 min to obtain a clear and transparent mixed solution B;
[0032] (104) Weigh 9.76 mg of p-phenylenediamine using a high-precision electronic balance and add it into a 150 mL beaker;
[0033] (105) 9.6 mL of acetonitrile was added to a beaker containing 9.76 mg of p-phenylenediamine;
[0034] (106) 50.4 mL of deionized water was added to a beaker containing 9.76 mg of p-phenylenediamine and 9.6 mL of acetonitrile solution;
[0035] (107) The obtained mixed aqueous solution was subjected to ultrasonic treatment for 30 min to obtain a clear and transparent mixed solution C;
[0036] (108) Using a dropper to draw up the mixed solution B and dropwise add it into the mixed solution C. The operation process requires that the dropping speed be uniform and slow, and that the solution be added dropwise to obtain a clearly stratified liquid with an upper layer of orange-yellow turbidity and a lower layer of transparent and clear liquid;
[0037] (109) The layered solution obtained in step 8 was sealed and allowed to react at room temperature for 72 h;
[0038] (110) After the reaction is allowed to stand at room temperature, carefully pipette the upper orange-yellow turbid liquid and the lower colorless transparent liquid of the layered solution that has reacted completely, and retain the product in the middle of the layer;
[0039] (111) The product collected in step 110 was transferred to a 50 mL centrifuge tube and centrifuged at 8000 rpm for 10 min, and the remaining liquid was discarded;
[0040] (112) Add acetone to a centrifuge tube and let it stand for 24 h. Centrifuge at 8000 r / min for 10 min and discard the liquid. Repeat this step three times.
[0041] (113) The solid obtained after step 112 was transferred to a 50-ml centrifuge tube, and deionized water was added and allowed to stand for 24 h. The mixture was then centrifuged at 8000 r / min for 10 min and the liquid was discarded. This step was repeated twice to obtain an orange-yellow TpPa-COF solid.
[0042] Preparation method of the TpPa-SO3H-COF material:
[0043] (201) Weigh 42 mg of trialdehyde phloroglucinol using a high-precision electronic balance and add it into a 250-mL beaker;
[0044] (202) 20 mL of n-octanoic acid was added to a beaker containing 42 mg of trialdehyde phloroglucinol;
[0045] (203) The obtained mixed solution of trialdehyde phloroglucinol and n-octanoic acid was ultrasonically treated for 30 min to obtain a clear and transparent mixed solution D;
[0046] (204) 56.4 mg of 2,5-diaminobenzenesulfonic acid was weighed using a high-precision electronic balance and added into a 150 mL beaker;
[0047] (205) 30 mL of deionized water was added to a beaker containing 56.4 mg of 2,5-diaminobenzenesulfonic acid;
[0048] (206) The obtained 2,5-diaminobenzenesulfonic acid aqueous solution was ultrasonically treated for 30 min to obtain a clear and transparent mixed solution E;
[0049] (207) Using a dropper, take the mixed solution D and add it dropwise to the mixed solution E. The operation process requires that the dropping speed be uniform and slow, and the solution be added dropwise to obtain a clearly stratified liquid with a dark purple clear upper layer and a transparent clear lower layer;
[0050] (208) The layered solution obtained in step 207 is sealed and allowed to react at room temperature for 72 hours;
[0051] (209) After the reaction is completed at room temperature, use a pipette to carefully pipette out the upper dark purple clear liquid and the lower clear liquid of the layered solution that has reacted completely, and keep the product in the middle of the layer;
[0052] (210) The product collected in step 209 was transferred to a 50 mL centrifuge tube and centrifuged at 8000 rpm for 10 min, and the remaining liquid was discarded;
[0053] (211) Add acetone to a centrifuge tube and let it stand for 24 h. Centrifuge at 8000 r / min for 10 min and discard the liquid. Repeat this step three times.
[0054] (212) The solid obtained after step 211 was transferred to a 50-ml centrifuge tube, and deionized water was added and allowed to stand for 24 h. The mixture was then centrifuged at 8000 r / min for 10 min and the liquid was discarded. This step was repeated three times to obtain a red flaky TpPa-SO3H-COF solid.
[0055] The preparation method of the TpPa-Py-COF material is:
[0056] (301) 11.5 mg of trialdehyde phloroglucinol was weighed using a high-precision electronic balance and added into a 250 mL beaker;
[0057] (302) 120 mL of n-octanoic acid was added to a beaker containing 11.5 mg of trialdehyde phloroglucinol;
[0058] (303) The obtained mixed solution of trialdehyde phloroglucinol and n-octanoic acid was ultrasonically treated for 30 min to obtain a clear and transparent mixed solution F;
[0059] (304) 8.5 mg of 2,5-diaminopyridine was weighed using a high-precision electronic balance and added into a 150 mL beaker;
[0060] (305) 120 mL of deionized water was added to a beaker containing 8.5 mg of 2,5-diaminopyridine;
[0061] (306) The obtained 2,5-diaminopyridine aqueous solution was ultrasonically treated for 30 min to obtain a clear and transparent mixed solution G;
[0062] (307) Using a dropper to draw up the mixed solution F and dropwise add it into the mixed solution G. The operation process requires that the dropping speed be uniform and slow, and that the solution be added dropwise, to obtain a clearly stratified liquid with a colorless, transparent, and clear upper layer and a purple-red, transparent, and clear lower layer;
[0063] (308) The layered solution obtained in step 308 is sealed and allowed to react at room temperature for 72 hours;
[0064] (309) After the reaction was completed at room temperature, the upper colorless transparent liquid and the lower colorless transparent liquid of the layered solution that had reacted completely were carefully pipetted with a dropper, and the product in the middle of the layer was retained. It was observed that a purple-red flaky solid was collected;
[0065] (310) The product collected in step 309 was transferred to a 50 mL centrifuge tube and centrifuged at 8000 rpm for 10 min, and the remaining liquid was discarded;
[0066] (311) Acetone was added to the centrifuge tube and allowed to stand for 24 h. The tube was centrifuged at 8000 r / min for 10 min and the liquid was discarded. This step was repeated three times.
[0067] (313) The solid obtained after step 311 was transferred to a 50-ml centrifuge tube, and deionized water was added and allowed to stand for 24 h. The tube was then centrifuged at 8000 r / min for 10 min and the liquid was discarded. This step was repeated three times to obtain a dark purple TpPa-Py-COF solid.
[0068] The origin of the name of TpPa-COF: trialdehyde pyrogallol is abbreviated as Tp in English, and p-phenylenediamine is abbreviated as Pa in English. The COF material generated by the reaction of the two is named TpPa-COF.
[0069] The origin of the name of TpPa-SO3H-COF: The English abbreviation of 2,5-diaminobenzenesulfonic acid is Pa-SO3H, and the COF material generated by the reaction with trialdehyde pyrogallol (English abbreviation Tp) is named TpPa-SO3H-COF.
[0070] The origin of the name of TpPa-Py-COF: The English abbreviation of 2,5-diaminopyridine is Pa-Py, and the COF material generated by the reaction with trialdehyde pyrrolidine (English abbreviation Tp) is named TpPa-Py-COF.
[0071] A method for preparing a power generation device, the method comprising the following steps:
[0072] S1: Transfer the TpPa-SO3H-COF material or TpPa-Py-COF material to a 100 ml beaker, add 50 ml of deionized water, and perform ultrasonic treatment on the solution in the beaker for 30 min to obtain a mixed solution A;
[0073] S2: Weigh 35 mg of silver nanoparticles into a 250 ml beaker using a high-precision electronic balance, add 190 ml of deionized water and 10 ml of isopropanol into the beaker to obtain a silver nanoparticle mixed solution with a concentration of 1.62 mmol / L, and perform ultrasonic treatment on the silver nanoparticle mixed solution for 30 min;
[0074] S3: Take an organic filter membrane and fix it at the filter position of the suction filtration device, fix a square waterproof plastic sheet with upper and lower rectangular filtration channels on the organic filter membrane, pour 35 ml of the silver nanoparticle mixed solution into it, and then transfer it to a blast drying oven and dry it at a drying temperature of 70°C for 10 minutes to obtain an organic filter membrane plated with a silver electrode;
[0075] S4: The organic filter membrane plated with the silver electrode obtained in step S3 is fixed at the filter of the suction filtration device, 50 ml of the mixed solution A is poured into it, and the mixed solution A is evenly distributed on the organic filter membrane and covers the silver electrode, and then the organic filter membrane is transferred to a blast drying oven and dried at a drying temperature of 100° C. for 10 minutes to obtain a power generation membrane;
[0076] S5: Fix two 30 cm copper wires on the silver electrodes on both sides of the power generation membrane, and finally use hot melt adhesive to reinforce and waterproof the connection between the copper wires and the power generation membrane to obtain a hydrovoltaic power generation device.
[0077] from Figure 1-3 It can be seen that the three pictures are the scanning electron microscope characterization results of TpPa-COF, TpPa-SO3H-COF and TpPa-Py-COF, and the three materials are evenly dispersed on the surface of the organic filter membrane, and the surface is flat;
[0078] from Figure 4 It can be seen that the characterization results of the X-ray diffraction patterns of the three materials show that the 2θ characteristic peaks of the three materials are obvious, indicating that the three materials were successfully prepared and have good crystallinity;
[0079] from Figure 5 It can be seen that the voltage output of the hydrovoltaic power generation devices based on three COFs materials, TpPa-COF, TpPa-Py-COF and TpPa-SO3H-COF, are 0.2, 0.5 and 1.4V respectively;
[0080] from Figure 6 It can be seen that the current output of hydrovoltaic power generation devices based on three COFs materials, TpPa-COF, TpPa-Py-COF and TpPa-SO3H-COF, are 2, 7 and 12 μA respectively.
[0081] Figure 7 The output voltage and current of the hydrovoltaic power generation device based on TpPa-SO3H-COF vary with the applied load.
[0082] Although the specific embodiments of the present invention have been described and illustrated in detail above, it should be noted that various changes and modifications may be made to the above embodiments without departing from the spirit of the present invention and the scope of the appended claims.
Claims
1. A hydroelectric power generation material, characterized in that: The hydrovoltaic power generation material is a TpPa-SO3H-COF material or a TpPa-Py-COF material prepared by replacing p-phenylenediamine with 2,5-diaminobenzenesulfonic acid or 2,5-diaminopyridine during the preparation of the TpPa-COF material.
2. A method for preparing a hydroelectric power generation device based on claim 1, characterized in that: The method comprises the following steps: S1: Transfer the TpPa-SO3H-COF material or TpPa-Py-COF material to a 100 ml beaker, add 50 ml of deionized water, and perform ultrasonic treatment on the solution in the beaker for 30 min to obtain a mixed solution A; S2: Weigh 35 mg of silver nanoparticles into a 250 ml beaker using a high-precision electronic balance, add 190 ml of deionized water and 10 ml of isopropanol into the beaker to obtain a silver nanoparticle mixed solution, and perform ultrasonic treatment on the silver nanoparticle mixed solution for 30 min; S3: Take an organic filter membrane and fix it at the filter of the suction filtration device, fix a waterproof plastic sheet on the organic filter membrane, pour 35 ml of the silver nanoparticle mixed solution into it, and then transfer it to a blast drying oven and dry it for 10 minutes to obtain an organic filter membrane plated with a silver electrode; S4: fix the organic filter membrane plated with silver electrodes obtained in step S3 at the filter of the suction filtration device, pour 50 ml of mixed solution A, let the mixed solution A be evenly distributed on the organic filter membrane and cover the silver electrodes, and then transfer the organic filter membrane to a blast drying oven and dry it for 10 minutes to obtain a power generation membrane; S5: Fix two 30 cm copper wires on the silver electrodes on both sides of the power generation membrane, and finally use hot melt adhesive to reinforce and waterproof the connection between the copper wires and the power generation membrane to obtain a hydrovoltaic power generation device.
3. A method for preparing a power generation device according to claim 2, characterized in that: The drying temperature of the blast drying oven in steps S3 and S4 is 70°C-100°C.
4. A method for preparing a power generation device according to claim 3, characterized in that: The concentration of the silver nanoparticle solution prepared in step S2 is 1.62 mmoL / L.
5. A method for preparing a power generation device according to claim 4, characterized in that: The shape of the waterproof plastic sheet is a square with upper and lower rectangular filtering spaces reserved.